The National Institutes of Health Human Microbiome Project. Issue 6 (December 2016) - Proctor, Lita M.
Summary: This overview describes the impetus for and the goals of the National Institutes of Health (NIH)'s Human Microbiome Project (HMP) and the research resources available through the HMP. As the HMP also serves as a catalyst for human microbiome research at the NIH, NIH Institutes and Centers support for this field is also briefly addressed.